Risk factors for length of NICU stay of newborns: A systematic review - Fu, Maoling; Song, Wenshuai; Yu, Genzhen; Yu, Yaqi; Yang, Qiaoyue (Frontiers in Pediatrics, 2023)
Background: The improvement in survival of preterm infants is accompanied by an increase in neonatal intensive care unit (NICU) admissions. Prolonged length of stay in the NICU (LOS-NICU) increases the incidence of neonatal complications and even mortality, places a significant burden on families' economic situation and healthcare systems. This review aimed to identify risk factors influencing LOS-NICU of newborns and to provide a basis for interventions to shorten LOS-NICU and avoid prolonged LOS-NICU. Methods: A systematic literature search was conducted in PubMed, Web of Science, Embase and Cochrane library for studies that were published in English from January 1994 to October 2022. The PRISMA guidelines were followed in all phases of this systematic review. The Quality in Prognostic Studies (QUIPS) tool was used to assess methodological quality. Results: Twenty-three studies were included, five of which were of high quality and 18 of moderate quality, with no low-quality literature. The studies reported 58 possible risk factors in six broad categories (inherent factors; antenatal treatment and maternal factors; diseases and adverse conditions of the newborn; treatment of the newborn; clinical scores and laboratory indicators; organizational factors). Conclusions: We identified several of the most critical risk factors affecting LOS-NICU, including birth weight, gestational age, sepsis, Necrotizing enterocolitis (NEC), Bronchopulmonary dysplasia (BPD) and Retinopathy of prematurity (ROP). As there were few high-quality studies available, well-designed and more extensive prospective studies investigating risk factors affecting LOS-NICU are still needed in the future.